Challenges of dual roles of marketing public relations and public relations in developing a positive image of PT. Overseas Zone - Siti Khopipah; Ade Tuti Turistiati (Universitas Negeri Yogyakarta, 2019)
The terms Marketing Public Relations and Public Relations are sometimes used interchangeably. However, actually the two roles are different. The purpose of this study is to analyse a dual role of Marketing Public Relations (MPR) and Public Relations (PR) in building a positive image of PT. Overseas Zone Education Consultant or PT. This research method uses a descriptive qualitative approach. Data collection techniques use observation, in-depth interviews, literature studies from books and relevant articles or documents. Researchers observed the Head of MPR who also plays a role as a PR in carrying out her daily work activities. In-depth interviews were conducted to 6 informants, namely the Head of MPR, the owner and head of the company, the Head of Consultant, 1 staff member, and 2 clients / customers. The results of this study show that Marketing Public Relations of PT. Overseas Zone carries out the process of planning and evaluating programs that can encourage purchases through an effective and trustworthy communication in conducting publications (special events). Strategies to support the role of Marketing Public Relations, namely through pull strategy, push strategy, and pass strategy. The dual role of MPR and PR that are occupied by a Head of MPR has obstacles in PT. Overseas Zone such as time constraints that cannot be managed properly in holding special events, more work, and fatigue because the energy devoted to these two roles is very large, the work is less optimal. This obstacle is a challenge for the Head of MPR who also act as a PR in building a positive image of the company. The company’s image is very dependent on the performance of the MPR. The solution made in overcoming obstacles in building a positive image of PT. Overseas Zone is to build good cooperation between the Head of MPR and education consultants. In addition, the company makes a new breakthrough by providing a study package product abroad that is different from other educational consulting services and target markets tailored to customer needs.Istilah Marketing Public Relations dan Public Relations kadang-kadang digunakan secara bergantian. Namun, sebenarnya kedua perannya berbeda Tujuan penelitian ini untuk menganalisis peran ganda Marketing Public Relations (MPR) dan Public Relations (PR) dalam membangun citra PT. Overseas Zone atau Overseas Zone Education Consultant. Metode penelitian ini menggunakan pendekatan kualitatif deskriptif. Teknik pengumpulan data menggunakan teknik observasi, wawancara mendalam dan studi literature. Peneliti melakukan observasi terhadap Head of MPR yang juga berperan sebagai PR dalam melaksanakan aktivitas pekerjaannya seharihari. Wawancara mendalam dilakukan terhadap 6 informan, yaitu Head of MPR, pemilik sekaligus pimpinan perusahaan, Head of Education Consultan, 1 orang staf, dan 2 orang client/customer. Hasil penelitian ini menunjukkan bahwa Marketing Public Relations di PT. Overseas Zone melakukan proses perencanaan dan evaluasi program-program yang dapat mendorong pembelian melalui komunikasi yang efektif dan dapat dipercaya dalam melakukan publikasi (special event). Strategi untuk mendukung peran Marketing Public Relations, yaitu melalui pull strategy, push strategy, dan pass strategy. Peran ganda MPR dan PR yang diampu oleh seorang Head of MPR memiliki hambatan di PT. Overseas Zone seperti kendala waktu yang kurang dapat dikelola dengan baik dalam mengadakan special event, pekerjaan lebih banyak, dan kelelahan karena tenaga yang tercurah untuk kedua peran tersebut sangat besar, hasil pekerjaan kurang optimal. Hambatan tersebut merupakan tantangan bagi Head of MPR yang merangkap sebagai PR dalam membangun citra positif perusahaan. Citra perusahaan sangat tergantung dari kinerja MPR. Solusi yang dilakukan dalam mengatasi hambatan dalam membangun citra positi PT. Overseas Zone adalah membangun sinergi yang baik antara Head of MPR dengan Head of Education Consultant. Selain itu, perusahaan membuat terobosan baru dengan menyediakan produk paket studi ke luar negeri yang berbeda dengan jasa konsultasi pendidikan lain dan target market disesuaikan dengan kebutuhan pelanggan.